Plant density and growth of forage maize genotypes. - Sánchez-Hernández, Miguel Ángel (2011)
A study was conducted to identify genotypes of maize withhigh forage potential. The fi rst experiment (E1) was conductedfrom November 2007 to February 2008, evaluating thegenotypes H-520, HE-1A17, HE-2A15, V-556AC, VS-536,A7573 and a native variety, at three densities (50000, 62500and 83333 plants/ha) and with four replications. In a secondexperiment (E2) (January to April 2009) the hybrids HE-1A17 and 2A15 were excluded and H-564C was added.The treatments were the combination of genotypes andsowing densities, in a randomized block design. Analysis ofvariance for each experiment were conducted, and combinedand comparison of means, by Tukey (P≤0.05). In the fi rstexperiment, the native genotype, average of densities, hadthe highest plant height (E1=247, E2=216 cm), total leafarea (E1=5834, E2=7516 cm2) and leaf area index (E1=3.8;E2=4.9), stem diameter (E1= 6.6; E2=7.5 cm) and forage yield(E1=44.3 t/ha). In the second experiment, H-564C (E2=36.6t/ha) surpassed the control. The density of 83333 plants/ha,average of genotypes, surpassed in forage yield (E1=35.8;E2=37.3 t/ha) the density of 62500 plants and 50000 plants/ha. For density, the maximum yield by genotype wasestablished at 83333 plants/ha in the native variety, whichproduced 57 t/ha of forage. On average of the densities, themaximum leaf area index was achieved with 83333 plants/ha,and the lowest was obtained with 50000 plants per hectare.